Osteoarticular disorders in sickle cell disease - Hasan, Syed Asif; Boeisa, Mahmood Ahmad; Alandunesi, Yazid Taha; Alshammari, Abdulkarim Thumayl; Calcattawi, Diyaa Hisham; Hejazi, Hamed Arif; Alshahrani, Nasser Mubarak; Alahmari, Abdullah Saeed; Alkishi, Malak Hussain; Alnawar, Yussif Mohammed; Alkanderi, Roaa Ali (International Journal Of Community Medicine And Public Health, 2021)
Different organs can be affected secondary to sickle cell disease, including the central nervous system, kidneys, gastrointestinal tract, respiratory system, cardiovascular system, bone, and joints. This can lead to increased morbidity and mortality events among the affected patients. Osteoarticular complications represent a severe set of events for patients with sickle cell disease. These complications might include gouty, septic, juvenile, and erosive arthritis, dactylitis, bone infarction, and osteomyelitis. These are the most common complications reported in the literature, and some case reports even reported other types of complications that develop secondary to the previously mentioned ones. Adequate diagnosis might be challenging in some cases. Therefore, clinicians must be crucial in determining the appropriate clinical and radiographic manifestations. Treating these cases is also challenging. Consequently, clinicians should be aware of these complications to enhance the prognosis of the affected patients. Further research is needed for the standardization of the diagnostic and management approaches in these events.